Dynamical screening function and plasmons in the wide HgTe quantum wells at high temperatures - Melezhik, E.O.; Sizov, F.F.; Mikhailov, N.N.; Gumenjuk-Sichevska, J.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
The dynamical screening function of a two-dimensional electron gas in a wide HgTe quantum well (QW) has been numerically modeled in this work. Calculations were performed in the Random Phase Approximation (RPA) framework and were based on the Lindhard equation. Our simulations directly incorporated the non-parabolicity of bulk 2D carriers’ spectrum, which was obtained by the full 8-band k.p method. Known from the literature are the data that transport properties of HgTe QWs can be explained by graphene-like screening. We carried out the comparison of the screening function for the Schrödinger fermions in the inverted bands HgTe QW with the appropriate screening function for the graphene monolayer with the Dirac fermions. In addition, the dependences of HgTe-specific screening function on temperature, scattering wave-vector, and frequency have been studied with the purpose of ascertaining the transport properties under high-frequency radiation for the QW structures to be used as THz detectors. Plasmon frequencies of 2DEG in HgTe quantum well under study were calculated in the long-wave limit for T = 77 K.